Opening the Doors to Agriculture: The Effect of Transparent Communication on Attitude - Joy N. Rumble; Tracy Irani (Journal of Applied Communications, 2016)
As consumers have become further disconnected from the agricultural industry, their concerns about agriculture have increased. Effective communication with consumers about agriculture has been identified as a potential solution to minimizing this disconnect. Transparent communication has been offered as a strategy to increase the effectiveness of industry communication. Therefore, this study sought to assess the effects of transparent communication and personal relevance, in a livestock production context, on the attitudes of college students. Elaboration Likelihood Model (ELM) and transparency served as the theoretical framework for this study. To fulfill the purpose of the research, an experimental design was used. The experimental treatments were tested with 688 college students through an online survey format. The results of the study found that both transparent communication and perceived transparency had a significant impact on attitude toward the communication, while personal relevance was not found to be significant. Further research examining transparent communication in ELM was recommended. In addition, it was recommended that practitioners implement transparent communication when communicating about the industry with those in the Millennial generation.
Keywords: Attitude; Elaboration Likelihood Model; Personal Relevance; Transparent Communication